2016
DOI: 10.1097/igc.0000000000000569
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Papillary Serous Carcinoma: A Single-Institution Review of 62 Cases

Abstract: Uterine papillary serous carcinoma is an aggressive variant of endometrial cancer associated with a high proportion of advanced-stage disease at diagnosis, high recurrence rates, and low OS. In our patients, prognosis was determined by myometrial invasion and International Federation of Gynecology and Obstetrics stage at diagnosis. Randomized trials in this area are required to clarify optimal adjuvant therapy for patients with UPSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
4
8
4
Order By: Relevance
“…Previous studies 4 , 5 , 7 , 9 , 26 33 have evaluated factors such as age, stage, tumor marker, depth of myometrial invasion, tumor size, lymph node involvement, lymphatic vascular space invasion (LVSI), and cytoreductive surgery as prognostic factors of UPSC, but their findings are inconsistent ( Table 6 ). However, most findings 4 , 7 , 9 , 27 , 29 31 showed that tumor stage and optimal cytoreduction strongly influence the prognosis of patients with UPSC, which was similar to our result. In the current study, we sought to define which traditional prognostic factors may be clinically important in UPSC patients, whereas multivariate analysis revealed that optimal cytoreduction and tumor stage were the only independent prognostic factors for both PFS and OS ( Table 3 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies 4 , 5 , 7 , 9 , 26 33 have evaluated factors such as age, stage, tumor marker, depth of myometrial invasion, tumor size, lymph node involvement, lymphatic vascular space invasion (LVSI), and cytoreductive surgery as prognostic factors of UPSC, but their findings are inconsistent ( Table 6 ). However, most findings 4 , 7 , 9 , 27 , 29 31 showed that tumor stage and optimal cytoreduction strongly influence the prognosis of patients with UPSC, which was similar to our result. In the current study, we sought to define which traditional prognostic factors may be clinically important in UPSC patients, whereas multivariate analysis revealed that optimal cytoreduction and tumor stage were the only independent prognostic factors for both PFS and OS ( Table 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…As for the evaluation of other histopathological factors, Slomovitz et al 9 showed that lymph node status, LVSI, and depth of myometrial invasion were all risk factors for a worse prognosis. While a series reported by Black et al 27 suggested that prognosis was only determined by myometrial invasion and tumor stage, a retrospective study conducted by Solmaz et al 28 demonstrated that LVSI is the only independent prognostic factor for OS, whereas LVSI and optimal cytoreduction are independent prognostic factors for PFS in patients with UPSC. The result of multivariate analysis of our study showed that there was no significant difference in survival based on age, depth of myometrial invasion, LVSI, and lymph nodes metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…In our research, compared with EAC, the prognosis of NEC was slightly worse. Compared with other studies, the survival rate of NEC patients in this study was higher [ 8 , 22 , 23 ]. The reasons were as follows: in this research, mixed cell carcinoma was defined as NEC, while studies had shown that the prognosis of mixed cell carcinoma was better than that of simple NEC [ 24 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Two different subtypes of EC have been described: type I tumours are mostly endometrioid adenocarcinomas and are associated with unopposed oestrogen stimulation and obesity and are often preceded by endometrial hyperplasia [2]. Type II tumours on the other hand are predominantly serous carcinomas, are commonly described as oestrogen independent arising in atrophic endometrium and are less well differentiated and therefore haver poorer prognosis [2,3]. The large majority of endometrial cancer are type I endometrioid, which is associated with good prognosis [4].…”
Section: Introductionmentioning
confidence: 99%